2016
DOI: 10.1002/pc.24043
|View full text |Cite
|
Sign up to set email alerts
|

Decorating wood flour/HDPE composites with wood veneers

Abstract: The low surface free energy makes wood plastic composites difficult to bond with traditional adhesives, such as urea formaldehyde resin (UF). This study investigates the decoration of wood flour/high‐density‐polyethylene composite (WF/HDPE) board with poplar wood veneers. High‐density polyethylene (HDPE) or maleic anhydride grafted polyethylene (MAPE) film was introduced between the veneer and the WF/HDPE composite board as an intermediate component to strengthen the bond. Surface bonding strength, hot water r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…7). Guo et al (2016) also reported that when the WF/HDPE panel was covered with the veneer by using the MAPE intermediate film, a new peak of an ester group located at 1,741.46 cm -1 was detected on the interface after pressing. A relatively low temperature is not enough to initiate the esterification reaction (Tang et al 2011), considering the heat loss during hot pressing and when board transferring from hot-press to cold-press.…”
Section: Effect Of Hot Pressing Conditions On Physical-mechanical Pro...mentioning
confidence: 90%
“…7). Guo et al (2016) also reported that when the WF/HDPE panel was covered with the veneer by using the MAPE intermediate film, a new peak of an ester group located at 1,741.46 cm -1 was detected on the interface after pressing. A relatively low temperature is not enough to initiate the esterification reaction (Tang et al 2011), considering the heat loss during hot pressing and when board transferring from hot-press to cold-press.…”
Section: Effect Of Hot Pressing Conditions On Physical-mechanical Pro...mentioning
confidence: 90%
“…[ 20 ] Additionally, grafted polyethylene film, such as maleic anhydride grafted polyethylene was also explored as an adhesive for overlaying WPC. [ 21 ] Using plastic film as an adhesive is clean and convenient. However, when the film with high melting points is used, WPC substrate tends to melt and degrade its mechanical properties, and more importantly, wood veneer on surface for decoration is prone to change in color at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Wood-based composites have been widely developed as alternative materials for furniture manufacturing or structure building board because of their stable physical properties and wide sources of raw materials (Zheng et al 2021;Lee et al 2011;Gao et al 2020). In order to obtain decorative and high value-added wood products, a sliced veneer with a thickness of 0.05$0.8 mm prepared from naturally precious wood is usually employed to overlay on the surface of wood-based panels (Guo et al 2018;Yu et al 2020;Zhang et al 2020;Wang et al 2020). Common precious tree species included Manchurian ash, oak, elm, black walnut, maple, teak, red sandalwood, and all the rest of it.…”
Section: Introductionmentioning
confidence: 99%